2022
DOI: 10.3390/molecules27206833
|View full text |Cite
|
Sign up to set email alerts
|

ZnO/Boron Nitride Quantum Dots Nanocomposites for the Enhanced Photocatalytic Degradation of Methylene Blue and Methyl Orange

Abstract: In this study, a heterostructure photocatalyst of ZnO nanoparticles decorated with boron nitride quantum dots (ZnO/BNQDs) was successfully synthesized by a simple solution procedure. The synthesized ZnO/BNQDs show that the BNQDs effectively suppress the recombination of photoinduced electrons and holes and the transfer of holes from ZnO nanoparticles by the formation of a heterojunction. The ZnO/BNQD nanocomposites thus demonstrate superior photocatalytic performances and excellent stability for the degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Radical trapping experiments were carried out to detect the photogenerated reactive species during the photocatalytic degradation of the EG dye [ 44 , 45 ]. We used ethylenediaminetetraacetic acid disodium (Na 2 EDTA) to capture holes, tert -butanol ( t BuOH) to capture hydroxyl radicals ( • OH), and para -benzoquinone ( p -BQ) for superoxide radical anions (O 2 −• ) during the photodegradation experiment of the EG dye in the presence of SnP@MCM−41 .…”
Section: Resultsmentioning
confidence: 99%
“…Radical trapping experiments were carried out to detect the photogenerated reactive species during the photocatalytic degradation of the EG dye [ 44 , 45 ]. We used ethylenediaminetetraacetic acid disodium (Na 2 EDTA) to capture holes, tert -butanol ( t BuOH) to capture hydroxyl radicals ( • OH), and para -benzoquinone ( p -BQ) for superoxide radical anions (O 2 −• ) during the photodegradation experiment of the EG dye in the presence of SnP@MCM−41 .…”
Section: Resultsmentioning
confidence: 99%
“…18 Liu et al synthesized BNQDs using the hydrothermal method from boric acid and melamine to be used as an active photocatalyst for dye removal by combining BNQDs with ZnO nanoparticles. 19 While many studies show that graphene quantum dots are associated with polymers, boron nitride quantum dots are still under investigation. Arthisree et al showed the effect of graphene quantum dots on the photoluminescence property of polyvinyl butyral nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Sert et al synthesized BNQDs by hydrothermal synthesis method using urea, boric acid and ammonia solution as starting materials to investigate antifouling properties by modification with polyethersulfone (PES) 18 . Liu et al synthesized BNQDs using the hydrothermal method from boric acid and melamine to be used as an active photocatalyst for dye removal by combining BNQDs with ZnO nanoparticles 19 . While many studies show that graphene quantum dots are associated with polymers, boron nitride quantum dots are still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…28 Liu et al synthesized a heterostructure photocatalyst based on ZnO nanoparticles decorated with BN QDs and reported that it exhibited exceptional photocatalytic performances and high stability for the degradation of MB and methyl orange under UV-light irradiation. 28 Xu et al investigated the photocatalytic activity of the BN/WO 3 hybrid material for rhodamine B, and even a small amount of BN was reported to be sufficient for enhanced photocatalytic activity compared to neat WO 3 . 27 According to Singh et al, the accumulation of SnO 2 on BN nanosheets provides a high surface area, transforming the particles into a suitable form for catalytic processing.…”
Section: ■ Introductionmentioning
confidence: 99%